Marxist Humanism and Ethics - Morkūnienė, Jūratė (Problemos, 1974)
The paper aims to make more precise the definition of Marxist humanism with a view of distinguishing its problems from the ones of Marxist ethics. The theory of Marxist humanism investigates regularities determining the all-round harmonious development of every individual whereas ethics studies regularities of morality as of a specific form of social consciousness. Marxist humanism is a criterion for determining the humaneness of the theory of morality and morality proper: moral improvement is but one aspect and indicator of the formation conditions for real humanism. The author points out that identification with and insufficient isolation of the theory of humanism from ethics leads to abstract humanism.